THE RELATIONSHIP BETWEEN MSME FINANCIAL REPORTING AND ACCOUNTING TRAINING FOR MSME’s - Kurniawan, Kurniawan; Sugiatmono, Bambang R (Laboratorium Riset Ekonomi, 2025)
Effective financial management for Micro, Small, and Medium Enterprises (MSMEs) is highly dependent on the preparation of quality financial statements. In an increasingly competitive business environment, accurate and transparent financial reports are crucial for business continuity and development. Accounting training is essential for improving the capability of MSME actors to prepare timely and accurate financial reports4. This literature review aims to identify the relationship between MSME financial reporting and accounting training based on relevant recent studies. By analyzing previous research, this review seeks evidence supporting the benefits of accounting training in enhancing financial report preparation skills, identifying best practices, and proposing strategies for improving the quality of MSME financial statements.